Low NDRG2 expression predicts poor prognosis in solid tumors: A meta-analysis of cohort study. Issue 41 (9th October 2020) - Gu, Aiqin; Xu, Jie; Ye, Jun; Zhang, Chuanmeng
Abstract: Background: As a member of the N-myc down-regulated gene family, N-Myc downstream-regulated gene 2 (NDRG2) contributes to the tumorigenesis of various types of cancers. However, the correlation between NDRG2 expression and the prognosis of solid tumor remains to be elucidated because of small sample sizes and inconsistent results in previous studies. In the present study, we conducted a systematic review and meta-analysis to explore the prognostic significance of NDRG2 in human solid tumors. Methods: PubMed, Web of Science, Embase, Chinese National Knowledge Infrastructure, and WanFang databases (up to April 2020) were searched for relevant studies that evaluated the impact of NDRG2 on clinical outcomes, including overall survival (OS), and disease-free survival (DFS), in solid tumors. Hazard ratios (HRs) with 95% confidence intervals (CIs) were pooled to assess the association between NDRG2 expression and the survival of patients with solid tumors. Odds ratios (ORs) with 95% CIs were pooled to estimate the correlation between NDRG2 expression and clinicopathologic characteristics in the patients. Results: A total of 13 eligible studies with 1980 patients were included in this meta-analysis. Low NDRG2 expression was significantly associated with poor OS (HR = 1.96, 95% CI: 1.60–2.40, P < .001) and DFS (HR = 2.70, 95% CI: 1.42–5.13, P = .002) in solid tumor. Furthermore, low NDRG2 expression was related to some phenotypes of tumor aggressiveness, such as clinical stage (OR = 3.21, 95% CI: 1.96–5.26, P < .001), lymph node metastasis (OR = 2.14, 95% CI: 1.49–3.07, P < .001), and degree of differentiation (OR = 0.60, 95% CI: 0.45–0.81, P = .001). Conclusions: NDRG2 may be a meaningful biomarker of poor prognosis and a potential therapeutic target for human solid tumors.